Designing a gold nanoparticle‐based nanocarrier for microRNA transfection into the prostate and breast cancer cells. (November 2014) - Ekin, Asli; Karatas, Omer Faruk; Culha, Mustafa; Ozen, Mustafa
Abstract: Background: Cancer is one of the most common causes of human deaths worldwide. Nanotechnology has the potential to facilitate the detection, diagnosis, and treatment of cancer cases. Successful delivery of nucleic acids into cancer cells with the use of nanoparticles would be a significant improvement for medical and cellular biology. The use of nanoparticle‐based vehicles in clinical treatment is considerably important for treating genetic disorders. Gold nanoparticles (AuNPs) have been suggested as therapeutic delivery tools for cancer. Because microRNAs (miRNAs), which induce post‐transcriptional gene silencing, are deregulated in cancer cells, they are also considered as strong candidates for cancer therapy applications. In prostate and breast cancer, miR‐145, a well‐known tumor suppressor miRNA, is strongly downregulated in tumor tissues compared to their corresponding normal tissues. Methods: In the present study, we aimed to use engineered AuNPs as nanocarrier platforms to deliver miRNAs to prostate/breast cancer cells. 13‐nm AuNPs were modified with thiolated RNAs and then the miR‐145 was hybridized to the RNAs that were chemically attached to the AuNPs. Results: The results obtained in the present study demonstrate the efficient delivery of miR‐145 to prostate/breast cancer cells. We also show that delivery was more efficient when the AuNP‐RNA‐miRNA carrier complex was formed at an elevated temperature of 72 °C. Conclusions: In conclusion, we show that AuNPs help the effective in vitro delivery of miR‐145 into cancer cells. Copyright © 2014 John Wiley & Sons, Ltd.